Why autonomy needs help. Issue 5 (15th February 2012) - Caplan, Arthur L
Abstract : Some argue that to be effective in healthcare settings autonomy needs to be strengthened. The author thinks autonomy is fundamentally inadequate in healthcare settings and requires supplementation by experience-based paternalism on the part of doctors and healthcare providers.